(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to evaluate the precision agriculture technology on the territory of Podlaskie Voivodeship. Research material consisted of data from the survey carried out in 100 randomly selected farms located in Podlaskie Voivodeship. The concept of “precision agriculture” is known among the surveyed farmers. Based on the research which was carried out, a relation between the surface area of the farm, education and age of respondents was reported. Precision agriculture technology is more popular among farmers who are less than 40 years old, who have higher education and big agricultural farms. Majority of farmers participating in the survey carries out regular research on the soil richness. Moreover, 46% uses in their farms modern technologies for plant production, only 10% uses the system of positioning and 8% of the investigated farms uses the system for guiding agricultural machines, 14% of the investigated farmers uses the system for parallel guiding of a tractor, less than 40% applies the system of variable dosing of fertilizers and plant protection substances. Majority of the investigated farmers claims that new technologies are necessary and they should be applied; however, they indicate too high costs and distribution of farms as the main reason for limitations.